The effects of customer accountability and knowledge sharing on voluntary organizations’ (VOs) effectiveness - Mohd Noor, N.H.; Siti Hajar, A.B.A.; Idris, M.A. (Emerald, 2017)
Purpose: This study aims to examine how the relationship between customer accountability and voluntary organizations’ effectiveness is mediated by knowledge sharing. Design/methodology/approach: Using a cross-sectional survey and a structured questionnaire, data were collected from 349 employees of Malaysian voluntary organizations (VOs). Baron and Kenny’s (1986) procedures for mediation testing were adopted for the main analysis. Findings: Results of structural equation modelling indicated that knowledge sharing partially mediates the relationship between and voluntary organizations’ effectiveness. Research limitations/implications: Despite the authors’ contribution on the current academia, this study only investigated 349 employees representing VOs located in a single area, which is the Klang Valley area, Malaysia. Further research could identify a larger sample that would strengthen the inferences and conclusions. Practical implications: The main practical implication is that Malaysian VOs need to be aware of the impact of customer accountability upon their voluntary organizations’ effectiveness, and they need to inculcate their employees’ knowledge sharing behaviour to foster the impact of customer accountability on voluntary organizations’ effectiveness. Originality/value: This paper is unique in that it is the first attempt to combine the previous direct effect relationship into a new model that shows the effect of customer accountability on voluntary organizations’ effectiveness and the role of knowledge sharing as a mediator in the context of Malaysian voluntary sector.